Perencanaan Sistem Pengukuran Kinerja Menggunakan Metode Balanced Score Card dan Performance Prism Melalui Analytical Hierarchy Process Sebagai Pertimbangan Keputusan Strategis (Studi Kasus: Pengukuran Kinerja Organisasi Pada STT MIGAS Balikpapan) - Arianti, Anggi Eka Putri; Hariastuti, Ni Luh Putu (ARIKA, 2025)
Designing the most effective performance measurement system used in an educational organization is not easy. Given that there are not many other studies that use the BSC and Performance prism methods simultaneously. Performance prism has several advantages including identifying stakeholders from many interested parties, such as owners and investors, suppliers, customers, workers, government, and the surrounding community. While BSC identifies stakeholders only from the stakeholder and customer side. The purpose of this study will be to design a performance measurement system by integrating the three methods, namely BSC and Performance prism for stakeholder satisfaction, as a consideration of strategic decisions will use the Analytical Hierarchy Process (AHP) method. The results of the study showed that the achievement of organizational performance was in the yellow category because it was in the index range of 4-8, which means that the organization's performance has not yet achieved the expected performance/not optimal. The achievement in the green category, it is in the index range of 8-10, which means that the organization's performance shows that STT Migas Balikpapan has good performance results so it needs to be maintained.